A randomized sham-controlled trial of manual acupuncture for infertile women with polycystic ovary syndrome - Wen Pan; Feng-xing Li; Qiao Wang; Zou-qin Huang; Yu-ming Yan; Ling Zhao; Xue-yong Shen (Integrative Medicine Research)
Background: Polycystic ovary syndrome (PCOS) is a complex polygenic disease and is one of the most common endocrinological and reproductive disorders. The purpose of this study was to evaluate the efficacy of acupuncture combined with herbal medicine among infertile females with polycystic ovary syndrome (PCOS). Method: A total of 86 women with PCOS, experiencing infertility, were recruited and randomly assigned to receive either manual acupuncture (MA) or sham acupuncture (SA) twice per week for three menstrual cycles. Both groups received herbal medication. The evaluations were conducted after three menstrual cycles and 24 weeks’ follow-up. Results: The trial was completed by 79 (91.86%) of the 86 randomly selected patients. During this study, the pregnancy rate in the MA group (46.34%) was significantly higher than the SA group (18.42%), with a P-value of 0.008. Moreover, the ovulation rate of the MA group (58.14%) was higher than that of the SA group (45.74%), with a P-value of 0.046. The improvement rate of PCOS score and testosterone level showed a statistical difference between the two groups (P-values were <0.05). There were no other differences between the two groups. Sex hormones level, including E2, T, P, LH, and LH/FSH were significantly lower after intervention in the MA group (P-values were <0.05) compared with baseline, while only the progesterone level was reduced in the SA group (P-value = 0.008). Conclusion: Manual acupuncture combined with herbal medicine may be clinically useful for infertile women with PCOS in improving pregnancy and ovulation rate. Trial Registration: Chinese Clinical Trial Registry: ChiCTR1800014997.